2004
DOI: 10.1080/02699200410001663362
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal patterns of tongue‐palate contact in the speech of individuals with cleft palate

Abstract: Individuals with cleft palate, even those with adequate velopharyngeal function, are at high risk for disordered lingual articulation. This article attempts to summarise current knowledge of abnormal tongue-palate contact patterns derived from electropalatographic (EPG) data in speakers with cleft palate. These data, which have been reported in 23 articles published over the past 20 years, have added significantly to our knowledge about cleft palate speech. Eight abnormal patterns of tongue-palate contact are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 28 publications
5
66
1
2
Order By: Relevance
“…Comparing subjects to idealized "normal" contact patterns may not be the most appropriate technique and may in fact undermine individual compensatory strategies. In fact, recent EPG investigations involving remediation of speech-language disorders have emphasized the importance of considering individual characteristics in speech production abilities as a predictive function influencing treatment success ͑e.g., Carter and Edwards, 2004;Gibbon, 2004͒. The findings of the present investigation confirm and extend those of our previous investigations ͑Baum and McFarland, 1997;McFarland, Baum, and Chabot, 1996͒, indi-cating substantial flexibility within the speech production system, permitting the majority of speakers to adapt to a significant oral-articulatory perturbation with ͑relatively͒ minimal practice. Interestingly, in contrast to the acoustic and perceptual results, the EPG data revealed few changes in tongue-palate contact over time, suggesting that compensatory adjustments for /s/ production were made by tongue shape changes in regions that did not contact the palate.…”
Section: B Epg Findingssupporting
confidence: 81%
See 1 more Smart Citation
“…Comparing subjects to idealized "normal" contact patterns may not be the most appropriate technique and may in fact undermine individual compensatory strategies. In fact, recent EPG investigations involving remediation of speech-language disorders have emphasized the importance of considering individual characteristics in speech production abilities as a predictive function influencing treatment success ͑e.g., Carter and Edwards, 2004;Gibbon, 2004͒. The findings of the present investigation confirm and extend those of our previous investigations ͑Baum and McFarland, 1997;McFarland, Baum, and Chabot, 1996͒, indi-cating substantial flexibility within the speech production system, permitting the majority of speakers to adapt to a significant oral-articulatory perturbation with ͑relatively͒ minimal practice. Interestingly, in contrast to the acoustic and perceptual results, the EPG data revealed few changes in tongue-palate contact over time, suggesting that compensatory adjustments for /s/ production were made by tongue shape changes in regions that did not contact the palate.…”
Section: B Epg Findingssupporting
confidence: 81%
“…In this way, compensatory tongue positioning can be recorded simultaneously with speech acoustics during the course of adaptation to a significant perturbation to oral form. Such compensatory responses can be compared to standard EPG appliances that involve a very thin layer of acrylic that has been shown to be relatively less perturbing to speech production than the thick palatal appliance ͑Hamlet, Cullison, and Stone, 1979͒. Electropalatography ͑EPG͒ is an extremely wellestablished measurement process that has been used both for understanding fundamental aspects of speech production and for clinical intervention to encourage appropriate tongue positioning for a variety of speech disorders, such as those associated with traumatic brain injury, velopharyngeal inadequacy/cleft palate, articulation disorders, deafness, and other communicative disorders ͑e.g., Flege, Fletcher, and Homiedan, 1988;Fletcher and Newman, 1991;Fletcher, McCutcheon, and Wolf, 1975;Gibbon, 2004;Gibbon and Wood, 2003;Goozée, Murdoch, and Theodoros, 2003;Parsloe, 1998͒. Tongue-palate contact patterns reflecting normal consonant and vowel articulation have been relatively well described using this technique and some studies have combined EPG analyses with more dynamic movement assessments such as by ultrasound ͑Stone, Faber, Raphael, and Shawker, 1992͒.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the results observed for children with or without craniofacial malformations indicate that other factors, in addition to dentofacial alterations, should be considered when investigating the occurrence of lisping in the child population, including immaturity of the oral motor sensory system 26 ; reduced tongue tonus due to obstructive mouth breathing, in the case of cleft palate 27 ; sensorial differences due to tissue handling (scars) in the case of cleft lip and palate 28 and hearing losses frequently observed in the child population, especially those with history of cleft palate 29,30 . Conversely, the possibility of efficient adaptation of children to the different structural conditions 31 may cause a less distorted speech, which would impair the auditory perception of lisping in the presence of facial deformity.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research has shown that a particular type of articulation error affecting vowels could be closely linked with increased nasalization (Gibbon et al, 2005). The error in question involves the tongue rising up to an abnormally high position during the production of some vowels, with the result that the tongue makes full contact against the palate (Gibbon, 2004;Gibbon et al, 2005). With the tongue pressed fully against the palate, air is unable to flow out of the mouth in the normal way and instead escapes through the nose.…”
Section: Introductionmentioning
confidence: 99%